‘Behind The Fence’—An Interdisciplinary Perspective - Váradi-Csema, Erika (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
The policy of a country’s legal area carries all the historical, legal history, political, socio-psychological, social, etc. the direct and indirect imprint of processes that it had to face in the past decades. This is also true for criminal policy. Moreover, there are few areas of law where the relationship between individual factors is so complex and multidirectional. The specific forms of state responses to crime and actions against behavior that offends or endangers society can change quickly, responding sensitively to society’s (perceived or real) expectations. After all, the basic phenomenon, the causes of crime, are also complex, and it is only possible to determine in retrospect which of the factors influencing illegal behavior played a specific role in its creation – at the same time, whether was the chosen criminal policy directions good. In the case of Central and East-European countries, however, there are common events that connect their past and present, and at the same time help us understand their responses to crime. Belonging to the former Soviet bloc can be considered as such – even if its ideological, political and economic influence was different in certain regimes. Similarly shared, mostly cataclysmic socio-psychological experience for the societies of these countries is system change and all its negative accompanying phenomena, from the economic crisis to the crisis of values and the loss of trust in state bodies. And although the accession to Council of Europe, and to the European Union (or its intention) provides a new common framework for the current existence of criminal policy, the strong demand for public safety remained a marked feature of this region. KEYWORDS: post-socialist countries, criminal policy, political and economic changes, social challenges, crisis of value